SARS-CoV-2 pseudovirus dysregulates hematopoiesis and induces inflammaging of hematopoietic stem and progenitor cells - Dong-Hoon Chae; Hyun Sung Park; Kyoung-Myeon Kim; Aaron Yu; Jae Han Park; Mi-Kyung Oh; Soon Won Choi; Jaechul Ryu; Cynthia E. Dunbar; Hee Min Yoo; Kyung-Rok Yu (Experimental and Molecular Medicine)
Abstract Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection primarily affects the respiratory system but may induce hematological alterations such as anemia, lymphopenia and thrombocytopenia. Previous studies have reported that SARS-CoV-2 efficiently infects hematopoietic stem and progenitor cells (HSPCs); however, the subsequent effects on hematopoiesis and immune reconstitution have not yet been described. Here we evaluated the pathological effects of infection of umbilical-cord-blood-derived HSPCs with the SARS-CoV-2 Omicron variant pseudovirus (PsV). Transcriptomic analysis of Omicron PsV-infected HSPCs revealed the upregulation of genes involved in inflammation, aging and the NLRP3 inflammasome, suggesting a potential trigger of inflammaging. Omicron PsV-infected HSPCs presented decreased numbers of multipotential progenitors (granulocyte‒erythrocyte‒macrophage‒megakaryocyte colony-forming units) ex vivo and repopulated primitive hematopoietic stem cells (Ki-67−hCD34+ cells) in an HSPC transplantation NOD-scid IL2rγnull mouse model (Omicron mouse). Furthermore, Omicron PsV infection induced myeloid-biased differentiation of HSPCs. Treatment with nanographene oxide, an antiviral agent, partially mitigated the myeloid bias and inflammaging phenotype both in vitro and in vivo. These findings provide insights into the abnormal hematopoietic and immune effects of SARS-CoV-2 infection and highlight potential therapeutic interventions.